Slavische Literaturen der Gegenwart als Weltliteratur Hybride Konstellationen - Hitzke, Diana; Finkelstein, Miriam (innsbruck university press, 2018)
World literature and translation, the world and the literary field as well as migration, translingual writing and hybridity are the topics of the present contributions to Slavic literatures of the present. The book combines analyzes of texts that have been written in Slavic, but also in non-Slavic languages ​​or in several languages ​​at the same time. Thus, works created in Russian, Bosnian-Croatian-Serbian, Polish, Czech, German, Tatar, English and French are associated with each other. The texts refer to global literary traditions, events and ways of life. However, they also respond to different local cultural and historical developments and social structures. On the one hand, the volume offers access to concepts of world literature and enriches the current debate on case studies from the Eastern European and Slavic contexts. On the other hand, he extends the Slavic discussion by dealing with theories and methods of world literature and the possibilities of their application to Slavic texts.